2018
DOI: 10.1002/chem.201800425
|View full text |Cite
|
Sign up to set email alerts
|

Porous Nanocomposite Comprising Ultralong Hydroxyapatite Nanowires Decorated with Zinc‐Containing Nanoparticles and Chitosan: Synthesis and Application in Bone Defect Repair

Abstract: Hydroxyapatite nanowires exhibit a great potential in biomedical applications owing to their high specific surface area, high flexibility, excellent mechanical properties, and similarity to mineralized collagen fibrils of natural bone. In this work, zinc-containing nanoparticle-decorated ultralong hydroxyapatite nanowires (Zn-UHANWs) with a hierarchical nanostructure have been synthesized by a one-step solvothermal method. The highly flexible Zn-UHANWs exhibit a hierarchical rough surface and enhanced specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…All above results indicated that Zn element was indeed embedded into the titanium substrate. Many studies have found the Zn element is essential for a variety of biological systems, including bone metabolism and dental development [29, 30]. Recent research has also considered it as an antioxidant to defend organism away from reactive oxygens [31].…”
Section: Resultsmentioning
confidence: 99%
“…All above results indicated that Zn element was indeed embedded into the titanium substrate. Many studies have found the Zn element is essential for a variety of biological systems, including bone metabolism and dental development [29, 30]. Recent research has also considered it as an antioxidant to defend organism away from reactive oxygens [31].…”
Section: Resultsmentioning
confidence: 99%
“…However, a donor organ is required for this purpose; and with respect to bone, autologous grafts (the best option for seeding) are not only limited in supply but also impose donor site problems. Instead, scaffolds are being fabricated from or coated with major components of bone ECM, such as HA or type I collagen, to generate bone-like tissue in vitro 2123 . Furthermore, 3D bioprinting with cell-loaded bioink is emerging as another attractive option 24 , albeit rooted in high-tech devices.…”
Section: Discussionmentioning
confidence: 99%
“…Through continuous efforts and attempts, this research team has successfully developed many kinds of fire-resistant paper with different functions and uses using ultralong HAP nanowires as the main building material. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] For example, the flexible fireproof inorganic nanocomposite paper as the protection layer in flame-retardant optical fiber cable, [25] fire-resistant inorganic analogous Xuan Paper with thousands of years' super-durability, [26] and highperformance filter paper for water purification. [27] In this work, a new kind of fire-retardant and high-temperature-resistant hydroxyapatite (HAP) nanowire/aramid label paper has been developed, the effects of the content of HAP nanowires on the mechanical strength, high-temperature resistance and flame-retardant performance of the as-prepared HAP nanowire/aramid label paper are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The high aspect ratio and hydroxyl groups of ultralong HAP nanowires make them interweave with each other and form hydrogen bonds, which is benefical for enhancing the mechanical properties of the fire‐resistant paper. Through continuous efforts and attempts, this research team has successfully developed many kinds of fire‐resistant paper with different functions and uses using ultralong HAP nanowires as the main building material . For example, the flexible fireproof inorganic nanocomposite paper as the protection layer in flame‐retardant optical fiber cable, fire‐resistant inorganic analogous Xuan Paper with thousands of years’ super‐durability, and high‐performance filter paper for water purification …”
Section: Introductionmentioning
confidence: 99%